UZBEK TRADITIONAL SINGING ART (Academia Science Repository, 2023)
It is known that the art of music performance is distinguished by the multiplicity of methods related to the interpretation of the performance, its stability and the characteristics of connecting with each other in its place. Certain aspects of Uzbek music performance traditions also require interpretation in this direction. First of all, the human voice is able to sing musical sounds meaningfully and perfectly through emotions. A singer's voice has timbre, which is formed by the combination of volume, pitch, hardness and all of them.